2020
DOI: 10.36959/545/381
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of New Mothers with Premature Babies in Neonatal Care Units: A Qualitative Study

Abstract: Preterm birth is a potentially stressful, an unexpected and a multi-problematic event such as neonatal respiratory problems, jaundice, hypotermia, feeding problems and infections [1][2][3][4]. After preterm delivery, as newborn need instantly stabilization (support respiratory and body term regulation etc.), they are generally admitted to the neonatal intensive care units (NICUs) [3,5]. Keeping mothers away from the NICU for reasons such as infection, noise, and privacy prevents mothers from getting closer to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
(41 reference statements)
2
6
0
Order By: Relevance
“…Previous evidence also indicated that the situation is stressful for parents. 15,16,24,38 Consistent with previous studies, uncertainty about the PTIs' condition, prognosis, and survival emerged as important stressors for parents. 16,17,27 Nevertheless, unlike a few previous studies in India 17 and Ethiopia, 38 the parents in this study did not mention stress arising from inadequate information.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Previous evidence also indicated that the situation is stressful for parents. 15,16,24,38 Consistent with previous studies, uncertainty about the PTIs' condition, prognosis, and survival emerged as important stressors for parents. 16,17,27 Nevertheless, unlike a few previous studies in India 17 and Ethiopia, 38 the parents in this study did not mention stress arising from inadequate information.…”
Section: Discussionsupporting
confidence: 80%
“…15,16,24,38 Consistent with previous studies, uncertainty about the PTIs' condition, prognosis, and survival emerged as important stressors for parents. 16,17,27 Nevertheless, unlike a few previous studies in India 17 and Ethiopia, 38 the parents in this study did not mention stress arising from inadequate information. Instead, their negative emotions emerged from information regarding the critical and unstable condition and the risk situation of the PTIs.…”
Section: Discussionsupporting
confidence: 80%
“…10,11 Mothers in present and previous studies experienced separation and inadequate attachment with their PTIs. 7,8,18,19 They also shared about limited visiting time and lack of opportunity to be close and hold their PTIs. Evidence of systematic review and other studies also indicated an inadequate conducive environment for mother-infant attachment.…”
Section: Discussionmentioning
confidence: 99%
“…Hilditch et al, (2019) argues that despite the small and Sick Babies often requiring inpatient care, neonatal intensive care is consistently associated with lower rates of breastfeeding initiation and duration and more uncertainty and stress. Pinar and Erbaba (2020) explored Experiences of New Mothers with Premature Babies in Neonatal Care Units in Turkey and results revealed that mothers whose babies were admitted to NICU were unable to breastfeed and establish intimacy with their babies and to communicate effectively with health care providers. According to a systematic review on barriers and facilitators for early and exclusive breastfeeding in health facilities in Sub-Saharan Africa, results show that facility-based breastfeeding policies and guidelines are available however, challenges in implementation exist, especially at lower health service levels and other challenges identified include health facility infrastructure, supplies, overcrowding and lack of privacy during breastfeeding counselling that lowers the openness and comfort of mothers (Kinshella et al, 2021).…”
Section: Background Informationmentioning
confidence: 99%
“…Some mothers turned to God Almighty for strength as they had limited options while some of the mothers had to find inner strength as they had limited or no support from the nurses or friends while others had peer support. Meanwhile a study by Pinar and Erbaba, (2020) revealed that mothers had to cope with the emotional stresses surrounding the neonatal ward experience through provision of milk to their infants. The difference in the results could be attributed to Zambian women perceiving provision of milk as a norm and not a coping strategy.…”
Section: Alternative Support Options While Breastfeeding In a Restric...mentioning
confidence: 99%